Macroscopy and Microscopy Study of Scopraia dulcis L. - Djoko Santosa; Subagus Wahyuono; Sugeng Riyanto; SM Widyastuti (Majalah Obat Tradisional, 2018)
A morphological diversity analysis of Scoparia dulcis by macroscopy and microscopy has been conducted. The aim of this research is to determine the morphological and anatomical character of S. dulcis which grow in Opak watershed, Special Region of Yogyakarta. Samples were taken from Sleman (Cangkringan, Ngemplak Kalasan, and Prambanan) and Bantul (Imogiri and Pundong) region. Selection of sampling location is based on altitude difference. The samples are the third leaf order from the tip of the stem. They were measured in length and width. Microscopy analysis was performed by observing the number of glandular trichomes, palisade cells in the epidermis and stomata in the upper and lower epidermis. The data obtained were analyzed using principal component analysis (PCA). The results show that based on morphological and anatomical assessment, there were found 3 clusters of S. dulcis, i.e. Cangkringan-Ngemplak-Prambanan, Kalasan, and Imogiri-Pundong cluster.